2017
DOI: 10.1002/nml.21263
|View full text |Cite
|
Sign up to set email alerts
|

Professionalization and Voluntary Transparency Practices in Nonprofit Organizations

Abstract: There are currently no public disclosure requirements for privately controlled charitable organizations in Germany. This study examines under which conditions German nonprofits, including both public charities and foundations, voluntarily choose transparency. Transparent nonprofits are defined herein as those that publicly disclose their annual reports and detailed financial information. A very small number of German nonprofits do so. The results of a crisp‐set Qualitative Comparative Analysis suggest that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
1
21
0
4
Order By: Relevance
“…While the GRI has received strong global support in academic literature (Brown, de Jong & Levy, 2009;Morhardt, Baird & Freeman, 2002), there is also a fair amount of criticism of this initiative (Boiral, 2013). Presently, many NGOs voluntarily disclose information on their ethical behaviour and their public relations regarding social and environmental issues (Striebing, 2017). Such disclosures enhance their corporate economic profile and credibility, reflecting the overall value of the institution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the GRI has received strong global support in academic literature (Brown, de Jong & Levy, 2009;Morhardt, Baird & Freeman, 2002), there is also a fair amount of criticism of this initiative (Boiral, 2013). Presently, many NGOs voluntarily disclose information on their ethical behaviour and their public relations regarding social and environmental issues (Striebing, 2017). Such disclosures enhance their corporate economic profile and credibility, reflecting the overall value of the institution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, other authors indicate that disclosure of voluntary information obeys to a motivation different to that stated above. For example, Striebing () affirms that “voluntary transparency is a management measure for nonprofit employees and managers to gain peer recognition within their professional community rather than to improve communication with the organization’s beneficiaries or within the wider community”. In any case, both the approach of this paper and that of Taylor and Warburton () are linked to another of the theories that can be used to explain information disclosure in nonprofits: legitimacy theory.…”
Section: Studies On Transparency In Ngosmentioning
confidence: 99%
“…An explanation of such an attitude should be sought in the management of an organisationthe professionalism of the management. Examining the circumstances under which organisations voluntarily choose to disclose their financial information, Striebing (2017) found that the wish of an organisation to voluntarily disclose its financial information might be explained by the professionalism of the organisation's management and stressed the role of a management comprehending and supporting the principles of professionalism and best practices.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the countries where no such an obligation has been imposed, information disclosure or undisclosed is a free choice of the organisation. As proved by some research investigations in Europe and America, the voluntary initiative to publish a financial report or disclose other financial information is quite low (Tremblay-Boire & Prakash, 2015;Striebing, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%